Chiral Phosphoric Acid‐Catalyzed Enantioselective Three‐ Component Aza‐Diels–Alder Reactions of Aminopyrroles and Aminopyrazoles. Issue 8 (13th May 2014) - Brioche, Julien; Courant, Thibaut; Alcaraz, Lilian; Stocks, Michael; Furber, Mark; Zhu, Jieping; Masson, Géraldine
<x xml:space="preserve">Abstract</x> The back cover picture, provided by Géraldine Masson, illustrates the straightforward three‐component process catalyzed by chiral phosphoric acid. The authors reveal the first use of aminopyrroles and aminopyrazoles as partners in the asymmetric three‐component Povarov reaction providing an access to novel chiral heterocyclic structures in excellent diastereoselectivities as well as good yields and enantioselectivities, as reported in the communication on pages 1719–1724 (J. Brioche, T. Courant, L. Alcaraz, M. Stocks, M. Furber, J. Zhu, G. Masson, Adv. Synth. Catal. 2014, 356, 1719–1724; DOI: 10.1002/adsc.201400093).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>